CHF ec STENOSIS AORTA ec RHD + PH SEKUNDER - Manullang, Doharjo; Tarigan, Menang Bastanta; Simanjuntak, Salomo G U; Situmeang, Ivonne; Simanjuntak, Evi Rosa; Hutahaeng, Reinhard DJ (Universitas Methodist Indonesia, 2025)
Stenosis is the most common valvular heart disease in Europe and North America with fear of calcification in the elderly (2-7% of the population> 65 years) while congenital aortic stenosis is usually caused by rheumatic heart disease which is now rare and usually found in young age. Classification of Aortic Stenosis. Classification of Aortic Stenosis can be divided based on the severity divided into 3 parts of mild, moderate, severe and very severe. Echocardiography modality is one of the gold standard tools for determining Aortic Stenosis which in echocardiography can capture Peak aortic jet velocity, the mean pressure gradient aortic valve area. The following is a case report of a 36 year old man with CHF ec Aortic Stenosis ec Rheumatic Heart Disease. This case was only diagnosed about 1 month ago with complaints of shortness of breath and chest pain. And the patient immediately went to RSMH for further treatment. This case was appointed for the management and preparation for surgery as a definitive therapy so that it is expected to give the best results in this patient